The entrepreneur's field guide : the 3 day startup method - Zimbroff, Andrew; Houser, Cam (Hackensack, New Jersey : World Scientific, 2021)
'This work covers developing high quality entrepreneurship curricula and implementation this curriculum in highly diverse settings around the world. As a result, all content will be highly robust, and will not be limited to any particular setting or location The book has easy-to-understand, actionable content that is robust enough for diverse entrepreneurial applications. It does not require prerequisite knowledge or skills to understand and apply all content contained in the work It is suitable for all current and aspiring entrepreneurs regardless of education and professional background'--
Includes bibliographical references and index.
Keywords: New business enterprises -- Handbooks, manuals, etc; Entrepreneurship -- Handbooks, manuals, etc